The Effect of Political Events on Financial Markets: A Case Study of Brexit - Danil Sushkov (Scientific Research and Experimental Development, 2024)
Political events have an important role in defining the global economic environment, with considerable implications for financial markets. These events can include elections, referendums, unexpected governmental decision-making, and foreign conflicts. Understanding how markets react to such occurrences is a critical component of financial analytics and economic prediction. Brexit, or Britain’s exit from the European Union, has been one of the most momentous political events of recent years. This process, which began with the referendum on June 23, 2016 and will conclude with the formal publication on January 31, 2020, has had a significant influence on the worldwide financial markets. The study of market reactions to Brexit enables scholars and practitioners to better understand risk transfer processes and the adaptation of financial instruments to new political circumstances. Recent studies shows that political events may cause large fluctuations in stock prices, volatility levels, and government bond rates. For example, studies of the Turkish market following unexpected government choices show that such events can produce dramatic variations in stock values and shifts in investor confidence. Similar studies done on the Sri Lanka Stock Exchange demonstrate that political concerns have a significant impact on asset prices and investor behavior. Brexit is a one-of-a-kind case study since it was not only unexpected, but it also has long-term implications for financial markets. According to research on market reactions to Brexit, this event resulted in a large rise in volatility as well as changes in stock prices and bond rates, making it a relevant topic for further investigation.